1994
DOI: 10.1080/02701367.1994.10607605
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Criterion-Referenced Standards for Tests of Arm and Shoulder Girdle Strength and Endurance

Abstract: The purpose of this study was to establish criterion-referenced standards for selected tests of arm and shoulder girdle strength and endurance for college females. Several popular tests of arm and shoulder girdle strength and endurance were administered to equal numbers of trained and untrained college females (N = 92) to generate data for the analysis. The contrasting groups method (Berk, 1976; Safrit & Wood, 1990) yielded the following criterion cutoff scores that classified college females as trained or unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…However, some studies also found that the hand-grip test was not valid [ 37 ], especially in accessing whole body muscle strength. Previous studies suggested that the knee bent push-up was a valid indicator of upper limb strength quality test [ 38 , 39 ]. Researchers used the 1 repetition maximum (1RM) leg extension test to assess the validity for lower-body muscular power and found that the standing long jump test can be a useful tool to assess lower-body muscular strength in children, but not whole body muscle strength [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies also found that the hand-grip test was not valid [ 37 ], especially in accessing whole body muscle strength. Previous studies suggested that the knee bent push-up was a valid indicator of upper limb strength quality test [ 38 , 39 ]. Researchers used the 1 repetition maximum (1RM) leg extension test to assess the validity for lower-body muscular power and found that the standing long jump test can be a useful tool to assess lower-body muscular strength in children, but not whole body muscle strength [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its importance, strength of the shoulder girdle has generally been evaluated manually using basic upper-extremity exercises [26,27]. shoulder girdle.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, shoulder girdle strength has been measured indirectly through basic exercises whose gross movements involve the shoulder muscles, such as pull-ups, push-ups, wall push-ups, scapular pinches, seated lat pull, seated chest press, and flexed arm hang [26,27]. More recently, a limited number of studies have considered the shoulder girdle more directly in strength measurements.…”
Section: An Apparatus and Protocol To Measure Shoulder Girdle Strengthmentioning
confidence: 99%
“…Other studies used cross-validation for a more accurate cutoff point, rather than ROC curve analysis [19]. Hooten et al used multiple variable linear regression for the relation between knee joint kinetics and pressure pain threshold [20].…”
Section: Roc and Non-roc-used Methods Or Analysis Of Criterion-referementioning
confidence: 99%